The Un/Bearable Lightness of (Slow) Watching: Audiovisual Boredom as Stimulation - Beata Zawadka (European Journal of American Studies)
The twenty-first century has seen the biggest breakthrough as regards the production and distribution of audiovisual culture. Slow cinema and serials—in particular those coming to us via streaming platforms as full seasons to binge-watch—are a special case of such a breakthrough for they offer us a new dynamics of experiencing culture; dynamics that relies on a meticulous orchestration of boredom to stimulate our creative participation in culture. This article will demonstrate, on the basis of selected Mubi, HBO, and Netflix productions, how the clever playing out of (serial) boredom can affect viewers’ mental, emotional, and even physical capacity and how important it is for a more effective perception of the twenty-first-century—digital—reality to be able to actively manage our “boredom-activated” culture compass.